Ion-Transfer Voltammetric Behavior of Propranolol at Nanoscale Liquid-Liquid Interface Arrays - Liu, Yang; Strutwolf, J.; Arrigan, Damien (American Chemical Society, 2015)
In this work, the ion-transfer voltammetric detection of the protonated β-blocker propranolol was explored at arrays of nanoscale interfaces between two immiscible electrolyte solutions (ITIES). Silicon nitride nanoporous membranes with 400 pores in a hexagonal arrangement, with either 50 or 17 nm radius pores, were used to form regular arrays of nanoITIES. It was found that the aqueous-to-organic ion-transfer current continuously increased steadily rather than reaching a limiting current plateau after the ion-transfer wave; the slope of this limiting current region was concentration dependent and associated with the high ion flux at the nanointerfaces. Electrochemical data were examined in terms of an independent nanointerface approach and an equivalent microdisc approach, supported by finite element simulation. In comparison to the larger interface configuration (50 nm radius), the array of 17 nm radius nanoITIES exhibited a 6.5-times higher current density for propranolol detection due to the enhanced ion flux arising from the convergent diffusion to smaller electrochemical interfaces. Both nanoITIES arrays achieved the equivalent limits of detection, 0.8 μM, using cyclic voltammetry. Additionally, the effect of scan rate on the charging and faradaic currents at these nanoITIES arrays, as well as their stability over time, was investigated. The results demonstrate that arrays of nanoscale liquid–liquid interfaces can be applied to study electrochemical drug transfer, and provide the basis for the development of miniaturized and integrated detection platforms for drug analysis.